Impaired Fibrinolysis in Obstructive Jaundice - Evidence from Clinical and Experimental Studies - Colucci, M; Altomare, D F; Chetta, G; Triggiani, R; Cavallo, L G; Semeraro, N (Thrombosis and Haemostasis, 1988)
Microvascular thrombosis is considered an important pathogenetic factor in renal failure associated with obstructive jaundice but the mechanisms leading to fibrin deposition are still unknown. The plasma levels of plasminogen activator inhibitor (PAI) in 29 patients with obstructive jaundice were found significantly increased as compared to 20 nonjaundiced patients. Fibrin autography of plasma supplemented with tissue plasminogen activator (t-PA) revealed that in icteric samples most of the added activator migrated with an apparent Mr of 100 kDa, corresponding to t-PA-PAI complex, whereas in control samples virtually all t-PA migrated as free enzyme. PAI activity detected in icteric samples is similar to the endothelial type PAI since it is neutralized by a monoclonal antibody against PAI-1.Venous stasis in jaundiced patients was neither associated with an increase in blood fibrinolytic activity nor with a decrease in PAI activity. Immunologic assay showed that t-PA release was impaired in 3 out of 4 patients. In controls, venous occlusion induced an increase in both fibrinolytic activity and t-PA antigen and a reduction in PAI activity. Bile duct recanalization in jaundiced patients subjected to surgery was accompanied by a decrease in plasma PAI activity which paralleled the decrease in serum bilirubin levels. In nonjaundiced patients, surgical treatment did not cause significant changes in either parameter. Rabbits made icteric by bile duct ligation showed an early and progressive increase in plasma PAI activity indicating that obstructive jaundice itself causes the elevation of circulating PAI. It is concluded that obstructive jaundice is associated with a severe impairment of fibrinolysis which might contribute to microvascular thrombosis and renal failure.
Keywords: PAI; t-PA; Obstructive jaundice; Thrombosis